PENGARUH BUDAYA ORGANISASI, PENGEMBANGAN KARIR, DAN EFIKASI DIRI TERHADAP KINERJA KARYAWAN PT. PLN (PERSERO) UNIT PELAYAAN JASA LOMBOK TENGAH - Mustaan Mustaan; Nizar Hamdi (Jurnal Inovasi Penelitian, 2022)
Abstract This study entitled "The Influence of Organizational Culture, Career Development, and Self-Efficacy on the Performance of Employees of PT. PLN (Persero) Central Lombok Service Service Unit”. The purpose of this study was to determine the effect of organizational culture, career development, and self-efficacy on employee performance. The population in this study were all employees of PT. PLN (Persero) UPJ Central Lombok amounted to 80 people, with a sample of 67 people. Based on the results obtained using multiple linear regression with the F test and t test, the Fcount value is 17.599 and Ftable is 2.742 with a significance level of 0.000 which is smaller than the probability coefficient of 0.05, meaning that simultaneously the variables of organizational culture, career development, and self-efficacy has a significant effect on employee performance (Y). While the partial test is known that organizational culture and career development variables have a significant effect on employee performance where tcount is 2,622 and 2,539 is smaller than ttable of 2,651 with probabilities of 0.011 and 0.014 smaller than = 0.05. Then the self-efficacy variable partially has a dominant significant effect on the employee performance variable because it is known that tcount of 3.459 is greater than ttable of 2.651 with a probability of 0.001 less than = 0.05.